CAN INORGANIC NITRATE/NITRITE EFFECTIVELY OVERCOME CHRONIC ANTHRACYCLINE CARDIOTOXICITY IN RABBITS?. (21st November 2014) - Lencova, O; Jirkovsky, E; Mazurova, Y; Adamcova, M; Chladek, J; Hroch, M; Simunek, T; Gersl, V; Sterba, M
Abstract : Inorganic nitrate/nitrite have been shown cardioprotective against ischemia-reperfusion injury and recently also against acute high-dose anthracycline (ANT) cardiotoxicity. However, translatability of the latter findings to clinically more relevant chronic ANT cardiotoxicity remains elusive. Hence, we wanted to clarify whether inorganic nitrate/nitrite may overcome chronic ANT cardiotoxicity just as effectively as dexrazoxane (DEX). Chronic cardiotoxicity was induced in rabbits with daunorubicin (DAU, 3 mg/kg, weekly for 10 weeks). Sodium nitrate was administered orally in the water (1 g/L), sodium nitrite (0.15 and 5 mg/kg) and DEX (60 mg/kg) were administered parenterally before each DAU dose. DAU induced significant decrease of LV systolic and diastolic function (p<0.05), rise of cardiac troponin T in plasma, serious degenerative changes and premature death. DEX effectively prevented all these changes, whereas nitrate supplementation had no impact on ANT cardiotoxicity. Similar results were also found in low-dose nitrite group. All animals receiving nitrite 5 mg/kg survived whole experiment, albeit with the significant decline in systolic as well as diastolic function. Morphological findings in this group resembled those in DAU group, but with lower total severity. Interestingly, several molecular parameters concerning apoptosis and mitochondria showed lower alterations in the LV myocardium of the nitrite groups, whereas number of other cardiotoxicity markers were not improved (e.g., HO1 or desmin expression). Inorganic nitrate and nitrite are unable to effectively prevent chronic ANT cardiotoxicity which contrasts with powerful cardioprotectant DEX. Supported by IGA NT13457-4-2012 and by the European Social Fund and state budget of the Czech Republic (CZ.1.07/2.3.00/30.0022).